Osteoid Osteoma of the Maxilla Presenting as Dental Implant Pain. (23rd July 2020) - Al Sadhan, R.; Alosaimi, A.; Al Shagroud, R.; Zaman, M. U.; Allahyani, M. S.
Abstract : Osteoid osteoma (OO) is a benign osteogenic lesion, regularly noticed in young individuals. A solitary lesion most frequently appears in long bones but is extremely rare in jawbones. Pain is a distinguishing characteristic of this lesion. Herein, we report a rare case of an OO in the right maxilla of a 37-year-old male presenting as pain associated with dental implants. Clinical and radiographic features were indicative of a benign neoplasia of boney origin. An excisional biopsy and histological examination of the lesion confirmed the diagnosis of osteoid osteoma. Surgical excision was followed by immediate relief of most of the pain. His follow-up visits were documented; complete relief of symptoms with no complications was observed during the postoperative period. There was no evidence of recurrence at a two-year follow-up. Osteoid osteoma of the maxilla may present as pain related to dental implants, and careful radiographic assessment of the entire jawbone should be considered if diagnosis of dental implant pain is unclear.